2016
DOI: 10.1167/iovs.16-19691
|View full text |Cite
|
Sign up to set email alerts
|

Thy-1 Regulates VEGF-Mediated Choroidal Endothelial Cell Activation and Migration: Implications in Neovascular Age-Related Macular Degeneration

Abstract: PurposeThis study addresses the hypothesis that age-related stresses upregulate Thy-1 in choroidal endothelial cells (CECs) and contribute to CEC activation and migration, processes important in choroidal neovascularization (CNV).MethodsMeasurements were made of Thy-1 protein (Western blot) in CECs and Thy-1 mRNA (real time quantitative PCR) in CECs treated with VEGF, CCL11, or PBS or in RPE/choroids from young or old donors or lasered or nonlasered mice. Immunolabeled Thy-1 in ocular sections was compared fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…; Wang et al . ). Macrophages infiltration into the adjacent sites of laser injury begins on the first day and peaks on the third to fifth day post laser photocoagulation (Sakurai et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Wang et al . ). Macrophages infiltration into the adjacent sites of laser injury begins on the first day and peaks on the third to fifth day post laser photocoagulation (Sakurai et al .…”
Section: Discussionmentioning
confidence: 97%
“…VEGF promotes the proliferation and migration of choroidal endothelial cells (CEC) (Wang et al . ) and disrupts the tight junction between RPE cells (Hartnett et al . ), thus facilitating growth of choroidal vessels into the subretinal space.…”
mentioning
confidence: 99%
“…The next GO term, called GO: 0005576 , describes a general term called extracellular region. Various extracellular substances participate in the pathogenesis of CNV, including LOX [ 63 ], LOXL2 [ 63 ], Thy-1 [ 64 ], and integrins [ 65 ]. Such specific substances may play irreplaceable roles during the initiation and progression of CNV; thus, this GO term that describes the extracellular regions of a certain focus is a potential CNV-associated biological process.…”
Section: Resultsmentioning
confidence: 99%
“…[6,[8][9][10] 7kCh activates three distinct kinase signaling pathways via NFkB, MAPK, and ERK to upregulate proinflammatory cytokines: IL-6, IL-8, and vascular endothelial growth factor (VEGF) which induce neovascularization in the choroid. [7,8,[11][12][13] In previous studies, retinal pigment epithelial (RPE) cells and vascular endothelial cells had an 8-to 10-fold increase in VEGF levels, [14] and a 2-fold increase in endothelial smooth muscle cells after exposure to 7kCh. [15] Our previous studies showed that in both ARPE-19 and rat neuroretinal R28 cell cultures, 7kCh significantly increased the levels of pro-apoptotic caspase-3, -8, and -12 activities.…”
Section: Introductionmentioning
confidence: 93%